Integrating Drosophila and Vibrio fischeri models for toxicity evaluation: uncovering detoxification trends in psoralea Fructus-TCM formulations - Zhang, Cheng; Li, Yina; Li, Fangyang; Dang, Wanyun; Shi, Zhuo; Yang, Chunqi; Xiao, Chengrong; Tang, Xianglin; Wang, Yuguang; Gao, Yue (Frontiers in Pharmacology, 2025)
BackgroundThe toxicity of herbal medicine combinations is critical to the clinical safety of traditional Chinese medicine (TCM). Current assessment methods are often inefficient and costly, creating an urgent need for new strategies to evaluate herbal medicine toxicity. We conducted research based on the commonly used TCM, Psoraleae Fructus (PF), and its formulations, Er Shen Pills (ESP) and Si Shen Pills (SSP).MethodsWe conducted a series of analyses on Drosophila, including survival analysis, enzyme assays, and quantitative PCR(qPCR) tests, to evaluate the effects of various TCM combinations on fruit fly health and viability. Transcriptome sequencing was utilized to investigate the detoxifying mechanisms of these combinations. Additionally, experiments with Vibrio fischeri assessed toxicity changes by calculating the luminescence inhibition rate. An innovative similarity model was developed to identify toxic components within the TCM formulations. Finally, molecular docking and molecular dynamics simulations explored the mechanisms of action of these toxic components on Vibrio fischeri, providing a comprehensive understanding at the molecular level.ResultsIn Drosophila experiments, ESP and SSP groups showed longer survival times, with male flies being more sensitive, making them more suitable for toxicity studies. Enzyme assays indicated a decreasing toxicity trend for ESP and SSP compared to PF, with significant changes observed in female flies. The qPCR analysis revealed that the upregulation of cpr and cyp6a8, along with the downregulation of keap1, hsp22, hsp68, gstD6, and hsp83, can assess the toxicity changes of PF, ESP, and SSP. The primary detoxification pathway involves the metabolism of xenobiotics by cytochrome P450. In the Vibrio fischeri assay, the IC50(50% inhibition) value of ESP was the highest, indicating reduced toxicity compared to PF. Screening for toxic components revealed that PF had 4, ESP had 16, and SSP had 22 components, primarily acting on LuxD, LuxE, and LuxG enzymes.ConclusionA method for detecting the toxicity variation patterns of PF, ESP, and SSP can be established using Drosophila and Vibrio fischeri, and the mechanisms of toxic effects can be explored respectively through transcriptomics and virtual screening techniques.